2017
DOI: 10.1016/j.pec.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Breaking bad news to patients with cancer: A randomized control trial of a brief communication skills training module incorporating the stories and preferences of actual patients

Abstract: Objective This study tested the effectiveness of a brief, learner-centered, breaking bad news (BBN) communication skills training module using objective evaluation measures. Methods This randomized control study (N=66) compared intervention and control groups of students (n=28) and residents' (n=38) objective structured clinical examination (OSCE) performance of communication skills using Common Ground Assessment and Breaking Bad News measures. Results Follow-up performance scores of intervention group stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
17

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(124 citation statements)
references
References 36 publications
(55 reference statements)
4
103
0
17
Order By: Relevance
“…Our results are also similar to the findings of Gorniewicz et al (2017), who studied the effect of an intervention using a BBN training module that incorporated patients' story preferences. They found that participants improved at their highest levels of CS with regard to "attention to patient responses after breaking bad news" and "communication related to patient emotions."…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results are also similar to the findings of Gorniewicz et al (2017), who studied the effect of an intervention using a BBN training module that incorporated patients' story preferences. They found that participants improved at their highest levels of CS with regard to "attention to patient responses after breaking bad news" and "communication related to patient emotions."…”
Section: Discussionsupporting
confidence: 87%
“…Some of them have evaluated subjective outcomes, such as trainees' satisfaction with the program and confidence in BBN (Orgel et al, 2010;Balzora et al, 2015;Reed et al, 2015;Schildmann et al, 2006). Other studies have evaluated objective outcomes, such as performance with standardized or much less frequently, real patients (Daetwyler et al, 2010;Szmuilowicz et al, 2010;Alexander et al, 2006;Yedidia et al, 2003;Lienard et al, 2010;Merckaert et al, 2013;Fallowfield et al, 2013;Gorniewicz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Oncotalk/VitalTalk teaching model is based on evidence-based principles and includes brief didactic sessions to provide specific communication skills, demonstration of those skills by faculties, intensive skill practice with simulated patients during which group and faculties give feedbacks to the trainee focusing on trainee's needs and attending to trainee's attitudes and emotions [13]. The survey was based on previously published researches exploring physician communication of bad news through self-administered questionnaires, investigating the attitudes and problems in disclosure BBN, perceived confidence and outcome of physicians' own communication skills, knowledge and self-efficacy about BBN, the usual practice, frequencies and format of communication with patients and/or family members [4,[14][15][16][17][18][19][20].…”
Section: Survey Instruments Clinician-perceived Communication Skills mentioning
confidence: 99%
“…Efforts must be made to encourage clinicians to address their patients' information and supportive needs, along with delivering adequate oncological care. Improved communication between cancer patients and their physicians could be achieved by developing training programmes focused on communication skills and, thus, achieve a better doctor-patient relationship (Gorniewicz et al, 2017;Kuzari, Biderman, & Cwikel, 2013;Thewes, Meiser, Rickard, & Friedlander, 2003).…”
Section: Several Patients Mentioned Not Being Informed In Detail Aboutmentioning
confidence: 99%